2020
DOI: 10.1038/s41598-020-77689-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and status of Lipoprotein (a) among Lebanese school children

Abstract: Lipoprotein a (Lp(a) is an independent risk factor for atherosclerotic cardiovascular disease. The prevalence of high Lipoprotein (a) (Lp(a)) in the Lebanese pediatric population is unknown. Our study aims to assess this prevalence and to study the relationship of Lp(a) with the lipid profile, age, body mass index (BMI) and socio-economic status (SES) in Lebanese schoolchildren. A total of 961 children aged 8–18 years (497 boys and 464 girls) were recruited from ten private and public schools in 2013–2014 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The population included in this study is a subgroup of our initial cohort. In our previous cross-sectional reports, 969 school children aged 8 to 18 years were recruited from 10 different private and public Lebanese schools using a stratified random sampling [23,44]. The schools were selected in the Greater Beirut and Mount Lebanon regions, where most of the Lebanese population is concentrated.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The population included in this study is a subgroup of our initial cohort. In our previous cross-sectional reports, 969 school children aged 8 to 18 years were recruited from 10 different private and public Lebanese schools using a stratified random sampling [23,44]. The schools were selected in the Greater Beirut and Mount Lebanon regions, where most of the Lebanese population is concentrated.…”
Section: Populationmentioning
confidence: 99%
“…BMI for sex and age below the 85th percentile was classified as normal, overweight was defined as BMI for sex and age between the 85th and 95th percentile, and obesity was defined as BMI for sex and age over the 95th percentile [45]. The population was categorized into three age groups: 8-11 years, 12-14 years, and 15-18 years as performed in our previous publications [23,44].…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Middle East is also a part of the world where dyslipidemia is highly prevalent [ 23 ]. In Lebanon, few cross-sectional studies looked at this prevalence in adult [ 24 , 25 ] or pediatric populations [ 26 , 27 ]. A single study published in 1999 on a population of a tertiary hospital staff found that the respective prevalence of high LDL-C levels and Lp(a) were 27% and 20% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A single study published in 1999 on a population of a tertiary hospital staff found that the respective prevalence of high LDL-C levels and Lp(a) were 27% and 20% [ 24 ]. In Lebanese children, the prevalence of high non-HDL-C and TG are, respectively, 9.2% and 26.6% [ 26 ], and the prevalence of high Lp(a) is 14.4% [ 27 ]. No other studies have evaluated the lipid profile (TC, HDL-C, TG, Lp(a), and PCSK9) in the Lebanese adult population and its relation to gender, age, and BMI.…”
Section: Introductionmentioning
confidence: 99%